IDENTIFICATIONS OF FACTORS BARRING STUDENTS FROM ASKING LECTURER AND THEIR SUBSTITUTE LEARNING STRATEGIES - Anita Wijayanti; Putu Putrayasa; Yohanes Bambang Gunawan (Wiralodra English Journal, 2023)
The focus of this qualitative study is to discover the factors that discouraged the students of Mahakarya Asia University from not asking questions to the lecturer in their English class despite their incomplete mastery of the lessons. Employing questionnaires and interview as the main instruments, the study found the triggering factors, with the first three being the fear of making a wrongly structured question, appearing unlettered after asking, and talking in front of other people. In addition, students’ inflexible adaptation to asking orally, which is different from asking in writing they adopted during COVID-19 remote learning, discourages them as well. Confusion on how and what to ask also stopped students from asking a question. To compensate for their deliberate abandonment of opportunities to ask a question, students carried out a variety of learning strategies. The most widely employed strategy to obtain the missing knowledge is to search for answers on internet due to its advantages: quick response, accurate answer, minimal effort, and available anywhere and anytime. Another learning strategy is discussion with other people. Discussion is opted because it is enjoyable, lively, and people can guess well what the students problems are from indirect clues. The last adopted strategy is to consult textbooks, notes, or other related materials as they contain the very topics of the lessons the students fail to understand. Keywords: discouraging factors to asking questions, substitute learning strategies, searching internet, discussion, reading modules